The Bioequivalence of Emulsified Isoflurane With a New Formulation of Emulsion: A Single-Center, Single-Dose, Double-Blinded, Randomized, Two-Period Crossover Study - Yang, Hui; Yin, Qinqin; Huang, Luying; Zhang, Min; Zhang, Xinxin; Sun, Qirong; Liu, Xuewei; Wang, Qi; Yang, Xi; Tan, Lingcan; Ye, Mao; Liu, Jin (Frontiers in Pharmacology, 2021)
Background: Emulsified isoflurane is a novel intravenous general anesthetic by encapsulating isoflurane molecules into emulsion. The formulation of emulsion has been improved according to the latest regulations of China Food and Drug Administration. This study was designed to compare the bio-equivalency of the new and previous formulation emulsion of isoflurane. Methods: In a single-center, single-dose, double-blinded, randomized, two-period crossover study, healthy volunteers received intravenous injection of 30 mg/kg of either isoflurane with either previous formulation of emulsion isoflurane (PFEI) or new formulation of emulsion isoflurane (NFEI). Arterial and venous blood samples were obtained for geometric mean test/reference ratios of Cmax, AUC0-t, AUC0-∞, as well as their 90% confidence interval (CI90) as the primary outcome. The secondary outcomes were safety measurements such as vital signs, 12-lead electrocardiography, adverse effects, laboratory tests; and anesthesia efficacy assessed by Modified Observer’s Assessment of Alertness/Sedation (MOAA/S) score, bispectral Index (BIS), and loss/recovery of eyelash reflex. Results: 24 subjects were eligible, of which 21 completed the whole experiment (NFEI n=21, PFEI n=23). Arterial geometric mean test/reference ratios of Cmax, AUC0-t, AUC0-∞ were 104.50% (CI90 92.81%~117.65%), 108.23% (94.51%~123.96%), and 106.53% (93.94%～120.80%), respectively. The most commonly seen adverse effects for NFEI and PFEI were injection pain (38.1% vs. 34.8%), hypotension (19.0% vs. 13.0%), apnea (14.3% vs. 17.4%), and upper airway obstruction (14.3% vs. 13.0%). No severe adverse effect was observed. The effectiveness of general anesthesia was similar between the two formulations. Conclusion: The CI90 of Cmax, AUC0-t, AUC0-∞, NFEI, and PFEI were within the range of 80%~125%, suggesting bio-equivalency between NFEI and PFEI. The safety and anesthesia effectiveness were also similar.